Acute Mesenteric Ischemia - Lendzion, Rebecca J.; Frahm-Jensen, Gert; Keck, James (Clinics in Colon and Rectal Surgery, 2022)
The surgical treatment of occlusive acute mesenteric ischemia (AMI) without revascularization is associated with an 80% overall mortality. Early diagnosis is crucial, and revascularization may reduce overall mortality in AMI by up to 50%. A diagnosis of AMI requires a high index of clinical suspicion and the collaborative effort of emergency department physicians, general and vascular surgeons, and radiologists. This article provides an overview of the etiology, physiology, evaluation, and management of acute mesenteric ischemia.
Keywords: acute mesenteric ischemia; nonocclusive mesenteric ischemia; mesenteric venous thrombosis; endovascular procedures; endovascular therapy; angioplasty; embolectomy; mechanical thrombolysis; surgical treatment